Pelaksanaan Reformasi Birokrasi di Badan Kepegawaian Daerah Kabupaten Kerinci Provinsi Jambi - Putra, Livia Sikmon (Jurnal Dinamika Sosial Budaya, 2022)
The poor performance of bureaucracy is what is then judged as a failure in the spirit of decentralization. Decentralization which is also a form of implementation of local democracy by utilizing the effectiveness of local government is also expected to encourage local governments to be more responsible in managing and providing services to the communities in the region. This is evident from the results of the study is known that in terms of the orientation of bureaucratic services, we still tend not to fully devote time and energy to carrying out the task of serving the people. This happens because in the placement of state apparatus is not placed in the right position but placed on not the expertise of the apparatus.